Brazilian’s Supreme Court in a Democratic Coup d’état - Maurício Sullivan Balhe Guedes; Luisa de Boucherville Ferreira Lombardi (Izzivi Prihodnosti, 2023)
Background and Originality: It is correct to say that Bolsonaro was not able to conceive his re-election bid as he would have liked, much of it due to the decision-making expansionism of the STF. The method employed does not necessarily see such a situation as negative, even if it is atypical, as long as it enhances democracy.